2013
DOI: 10.1016/j.meegid.2013.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and population genetics of Leishmania infantum genotypes in São Paulo State, Brazil, employing multilocus microsatellite typing directly in dog infected tissues

Abstract: This study investigated the genetic characteristics of Leishmania infantum samples from São Paulo (SP) State, Brazil in order to collaborate with information about the possible origins of the parasites, as well as, the introduction and spread of visceral leishmaniasis in this Brazilian State. Multilocus microsatellite typing (MLMT) was performed using a set of 17 microsatellite markers. DNA was extracted from 250 samples collected from dogs diagnosed with visceral leishmaniasis and 112 (45%) were genotyped: 67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 47 publications
4
26
0
3
Order By: Relevance
“…We were able to detect two genetically isolated populations of L. (L.) major in Sindh province, Pakistan. Furthermore, our results corroborated the possibility and/or usefulness of genotyping L. (L.) major directly from clinical samples [33,34]. A comprehensive study of the epidemiology of CL in Pakistan, including more strains from other regions endemic for CL and investigations of possible differences in reservoirs and sand fly vectors, is warranted.…”
Section: Discussionsupporting
confidence: 75%
“…We were able to detect two genetically isolated populations of L. (L.) major in Sindh province, Pakistan. Furthermore, our results corroborated the possibility and/or usefulness of genotyping L. (L.) major directly from clinical samples [33,34]. A comprehensive study of the epidemiology of CL in Pakistan, including more strains from other regions endemic for CL and investigations of possible differences in reservoirs and sand fly vectors, is warranted.…”
Section: Discussionsupporting
confidence: 75%
“…The West-to-East expansion of human VL in Mato Grosso do Sul was properly demonstrated by Correa-Antonialli et al (2007) [42] who pointed to the construction of the Bolivia-Brazil gas pipeline as a possible cause for the VL time and space expansion. This same hypothesis was considered to explain the spread of the canine and human disease in the west region of São Paulo [12, 38]. Finding the same pheromone type in males in the same temporal expansion route from West to East in São Paulo State may also support the hypothesis that the ( S )-9-methylgermacrene-B L .…”
Section: Discussionmentioning
confidence: 56%
“…i . chagasi , identified by multilocus microsatellite typing, isolated from dogs from Northwest and Southeast regions of the São Paulo State [38] show distribution coinciding with the two L . longipalpis chemotype populations distribution presented here.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Motoie et al [56] identified the presence of genetically distinct populations of L . (L . )…”
Section: Discussionmentioning
confidence: 99%